Энергетика и окружающая среда – информационные аспекты - Макаровский, Е. Л. (НТУ "ХПИ", 2006)
The information demands of management of a regional fuel and energy complex are described from the point of view of ecological safety of territory. Influencing of a fuel and energy complex of the Kharkov oblast on an ambient environment is estimated. The problems of an information supply of development of alternate power engineering in region are described. The most perspective for realization of these problems information technologies are described
Keywords: природная среда; топливно-энергетический комплекс; технологии информационные; экологическая безопасность; экономика; ГИС-технологии; антропогенная нагрузка; альтернативная энергетика